The Challenges of Effective Teaching and Learning of English in Public Secondary Schools in Nigeria - Oladayo, Murana Muniru (International Journal of Educational Studies, 2021)
The strategic place of English language in national development and mutual co-existence of Nigerians is not debatable. English has become a foreign national language to which the destiny of Nigeria is inextricably tied. The teaching of English at all levels of education in Nigeria is bedeviled with certain debilitating challenges. This paper examines some of the challenges of teaching and learning English in public secondary schools in Nigeria. It identifies such problems as poor quality of pupils admitted to secondary school, incompetent teachers of English, poor methodology and lack of motivation among others. The paper concludes that effective teaching of English language is a sine qua non for meaningful development in Nigeria and emphasizes the need for collective efforts in this direction. It recommends better training and retraining of teachers through continuing professional development practices and better commitment on the part of the government to the course of English studies in schools in Nigeria.